Adoption of Improved Poultry Technologies amongst Members of Poultry Producer Company and Non-member Women Farmers of Madhya Pradesh, India - Patel, Raj K.; Chander, Mahesh; Verma, Med R.; Johnson, Demian C. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Poultry Producer Company is collectivizing the smallholder poultry farmers and helps them to perform poultry farming scientifically  and efficiently. The present study was conducted on women poultry farmers of Madhya Pradesh to study the impact of poultry producer  company on the adoption of improved technologies of poultry farming amongst smallholder farmers. Ex-post facto research design was  used in the study. Multistage sampling was done for the selection of respondents and a total of 140 members and 140 non-member  women farmers were selected randomly for data collection. After the application of propensity score matching, 96 members and 96  non-members were found suitable for data analysis and interpretation of results. It was found that the majority of the members had  high level of adoption of improved poultry technologies while majority of non-members had medium level of adoption of poultry  technologies. The adoption quotient for member and non-member farmers was 83.75 and 37.92%, respectively. There was a significant  difference in the overall adoption rate of members compared to non-members at 0.1% significance.
Keywords: Adoption; Improved Poultry technologies; Poultry Producer company; Women Poultry